Evolutionary Dynamics of the OR Gene Repertoire in Teleost Fishes: Evidence of an Association with Changes in Olfactory Epithelium Shape. (5th May 2021) - Policarpo, Maxime; Bemis, Katherine E; Tyler, James C; Metcalfe, Cushla J; Laurenti, Patrick; Sandoz, Jean-Christophe; Rétaux, Sylvie; Casane, Didier
Abstract: Teleost fishes perceive their environment through a range of sensory modalities, among which olfaction often plays an important role. Richness of the olfactory repertoire depends on the diversity of receptors coded by homologous genes classified into four families: OR, TAAR, VR1, and VR2. Herein, we focus on the OR gene repertoire. While independent large contractions of the OR gene repertoire associated with ecological transitions have been found in mammals, little is known about the diversity of the OR gene repertoire and its evolution in teleost fishes, a group that includes more than 34, 000 living species. We analyzed genomes of 163 species representing diversity in this large group. We found a large range of variation in the number of functional OR genes, from 15 in the Broad-nose Pipefish Syngnathus typhle and the Ocean Sunfish Mola mola, to 429 in the Zig-zag Eel Mastacembelus armatus . The number of OR genes was higher in species when a multilamellar olfactory rosette was present. Moreover, the number of lamellae was correlated with the richness of the OR gene repertoire. While a slow and balanced birth-and-death process generally drives the evolution of the OR gene repertoire, we inferred several episodes of high rates of gene loss, sometimes followed by large gains in the number of OR genes. These gains coincide with morphological changes of the olfactory organ and suggest a strong functional association between changes in the morphology and the evolution of the OR gene repertoire.